Is Prevention Better Than Cure? - Russell, Louise B. (Rowman & Littlefield Publishers, 2010)
A growing body of research indicates that prevention offers the promise of better ways to maintain health and extend life. In this timely volume, Louise B. Russell shows that preventive measures are not as simple as often depictedwhile many do improve health, they are not without risk or cost, and in fact rarely reduce medical expenditures. Each measure, she argues, must be evaluated individually and in all its dimensions: health benefits, health risks, and resource costs. To demonstrate the many factors involved in evaluating preventive measures, Russell examines the policy debates about smallpox and measles vaccination, screening and drug therapy for hypertension, and exercise. She uses these case studies to explain the methods of cost-effectivness analysis, showing how the choice among health investments can be made a more rational exercise. The volume concludes with a suggested framework for the design of future cost-effectiveness evaluations. Policymakers in and out of the health field will benefit from this lucid examination of the potential of prevention for improving health and changing the allocation of limited resources.